The Digital Divide and Seeking Health Information on Smartphones in Asia: Survey Study of Ten Countries - Xiaohui Wang; Jingyuan Shi; Kwan Min Lee (JMIR Publications, 2022)
BackgroundAlthough recent developments in mobile health have elevated the importance of how smartphones empower individuals to seek health information, research investigating this phenomenon in Asian countries has been rare. ObjectiveThe goal of our study was to provide a comprehensive profile of mobile health information seekers and to examine the individual- and country-level digital divide in Asia. MethodsWith survey data from 10 Asian countries (N=9086), we ran multilevel regression models to assess the effect of sociodemographic factors, technological factors, and country-level disparities on using smartphones to seek health information. ResultsRespondents who were women (β=.13, P<.001), parents (β=.16, P<.001), employed (β=.08, P=.002), of higher social status (β=.08, P<.001), and/or from countries with low health expenditures (β=.19, P=.02) were more likely to use smartphones to seek health information. In terms of technological factors, technology innovativeness (β=.10, P<.001) and frequency of smartphone use (β=.42, P<.001) were important factors of health information seeking, whereas the effect of online information quality was marginal (β=-.04, P<.001). ConclusionsAmong smartphone users in Asia, health information seeking varies according to individuals' socioeconomic status, their innovativeness toward technology, and their frequency of smartphone use. Although smartphones widen the digital divide among individuals with different socioeconomic status, they also bridge the divide between countries with varying health expenditures. Smartphones appear to be a particularly useful complement to manage health in developing countries.